Robustness of Mammalian Gut Microbiota to Humanization in Captivity - Trevelline, Brian K.; Moeller, Andrew H. (Frontiers in Ecology and Evolution, 2022)
In mammals, the composition of the gut microbiota is associated with host phylogenetic history, and these host-lineage specific microbiota have been shown, in some cases, to contribute to fitness related traits of their hosts. However, in primates, captivity can disrupt the native microbiota through a process of humanization, in which captive hosts acquire gut microbiota constituents found in humans. Despite the potential importance of this process for the health of captive hosts, the degree to which captivity humanizes the gut microbiota of other mammalian taxa has not been explored. Here, we analyzed hundreds of published gut microbiota profiles generated from wild and captive hosts spanning seven mammalian families to investigate the extent of humanization of the gut microbiota in captivity across the mammalian phylogeny. Comparisons of these hosts revealed compositional convergence between captive mammal and human gut microbiota in the majority of mammalian families examined. This convergence was underlain by a diversity of bacterial lineages, including members of the Archaea, Clostridium, and Bacteroides. However, the gut microbiota of two families—Giraffidae and Bovidae—were remarkably robust to humanization in captivity, showing no evidence of gut microbiota acquisition from humans relative to their wild confamiliars. These results demonstrate that humanization of the gut microbiota is widespread in captive mammals, but that certain mammalian lineages are resistant to colonization by human-associated gut bacteria.